Applicability of International Accounting Standards in Public Sector IPSAS and its Impact on Quality of Financial Reporting in Iraq: Applied Study in Iraqi Government Institutions - Zina Adnan Kareem (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The research aims to demonstrate the extent to which international accounting standards can be applied in the public sector. IPSAS And its impact on the quality of financial reporting in Iraq and providing a theoretical framework on the concept of international accounting standards in the public sector IPSAS The quality of financial reporting in Iraq and identifying the economic and social benefits of implementing it IPSAS In Iraqi government institutions and evaluating the positive impact of the application IPSAS on the local economy and society and studying the most important challenges that may hinder the implementation IPSAS and to provide recommendations to overcome them, the deductive approach was relied upon in building the proposed framework for the research by moving from the general to the specific and relying on the inductive approach by moving from the specific to the general by generalizing the conclusions and recommendations to the research community. The research community is represented by all government departments and institutions in Iraq. As for the research sample, the Financial Supervision Bureau was chosen because of the effective role of this body in imposing accounting and control systems on government departments and institutions, preserving public money, supporting public accountability and strengthening the economy. The most significant of the researcher's findings, however, was that the Iraqi Accounting Standards Board had failed to implement international accounting standards. the public sector and issue local standards that are consistent and compatible with the above standards to bridge the large gap between international and Iraqi standards because the current local rules are insufficient to address accounting practices.